Food without fear : identify, prevent, and treat food allergies, intolerances, and sensitivities - Gupta, Ruchi (Ruchi S.); Loberg, Kristin (Hachette Go, 2021)
"A world-renowned researcher and physician offers the first book to identify the entire spectrum of food-related health conditions, from allergy to sensitivity, and what we can do about it. Allergies are an epidemic--but they don't have to be. Every day, more than five hundred people in the US go to the emergency room following a bad allergic reaction to food; 1 in 10 people have food allergies--and they are acute, alarming, and can be life-threatening. These are just a few of the statistics that prove what most of us know anecdotally: food allergies are on the rise. But allergy itself is just the tip of the iceberg--and it's not just a problem for kids: there is a whole spectrum of food-related conditions, including sensitivities, intolerances, and challenges. 1 in 5 people have food intolerances or sensitivities, and while these can be debilitating, they are chronic and can also be life-threatening in the long-term. Additionally, there are several autoimmune disorders that can masquerade as allergic disease. This means a lot of confusion, potential misdiagnoses, and incorrect or poor care. But there is good news: Dr. Ruchi Gupta is on the front lines of this epidemic; in her first book, she shares revolutionary research from her lab to address the entire spectrum of food-related health conditions. This panoramic view of food challenges empowers readers, arming them with the info to ask the right questions and get a proper diagnosis. From debunking common myths (an allergy and an intolerance aren't the same thing--and both can have life-threatening effects) to understanding masqueraders, to learning about triggers (including environmental factors), Dr. Gupta tells you all you need to know. Using a framework of identify, empower, manage, prevent, and treat, Food Without Fear offers hope and help to the millions of people who are affected. Food doesn't have to be an enemy"--